1997
DOI: 10.3109/09687689709048174
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatation, fusion and aqueous content release from liposomes induced by lysozyme derivatives: Effect on the lytic activity

Abstract: Chemically modified lysozymes, namely: N-succinyl lysozyme, glycine methyl ester of N-succinyl lysozyme and oxoindole lysozyme have been prepared. Aggregation, fusion and leakage of phospholipid vesicles induced by these derivatives have been studied in comparison with the effect of the unmodified protein. The experiments were carried out with negatively charges 9PC/PA, 9:1) and uncharged (PC and PC/DOPE/Chol (10:5:5)) lipid vesicles of different packing. Fusion and aggregation of negatively charged phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[4][5][6] HEWL is structurally homologous to human lysozyme, involved in several destabilizing mutations-related to protein deposition into amyloid plaques found in the liver, kidneys, and spleen of patients affected by non-neuropathic hereditary amyloidosis. [7][8][9][10][11] Because of its homology to human lysozyme, HEWL has been extensively used as a model in studies for a number of investigations: protein adsorption at interfaces, 12,13 membrane fusion, [14][15][16][17] protein folding and aggregation into amyloids. [18][19][20][21] Human lysozyme forms amyloid fibrils in vitro upon incubation at low pH and elevated temperature, 22,23 whereas HEWL forms amyloid fibrils when incubated in organic solvents 24 or in the presence of negatively charged lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] HEWL is structurally homologous to human lysozyme, involved in several destabilizing mutations-related to protein deposition into amyloid plaques found in the liver, kidneys, and spleen of patients affected by non-neuropathic hereditary amyloidosis. [7][8][9][10][11] Because of its homology to human lysozyme, HEWL has been extensively used as a model in studies for a number of investigations: protein adsorption at interfaces, 12,13 membrane fusion, [14][15][16][17] protein folding and aggregation into amyloids. [18][19][20][21] Human lysozyme forms amyloid fibrils in vitro upon incubation at low pH and elevated temperature, 22,23 whereas HEWL forms amyloid fibrils when incubated in organic solvents 24 or in the presence of negatively charged lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, many studies have shown the ability of lysozyme to bind lipid bilayers with a high affinity to negatively charged phospholipid vesicles favoured by its net positive charge over a broad pH range. 20,21,[24][25][26][27][28][29][30] The data presently available indicate that lysozyme association with phospholipid bilayers involves both electrostatic and hydrophobic interactions (reviewed in ref. 31) and modulates its aggregation propensity.…”
Section: Introductionmentioning
confidence: 99%
“…27 The model, subsequently adapted for Annexin V-induced aggregation and fusion of PS vesicles, 28 envisages a change in solvent structure in the contact region between the protein and membrane surface upon lysozyme binding. Actually, at low pH values the massive presence of bound lysozyme molecules induces a strong dehydration of the lipid membrane surface; the latter most likely results from disruption of membrane integrity due to pH-and ionic strengthdependent protein penetration inside the bilayer, 20 with changes in liposome permeability 29 and liposome fusion. 30,32 These data have been confirmed and extended by a recent RET-based study; 33 the latter showed that both lysozyme location at the lipid-water interface and its penetration inside the bilayer depend on protein coverage of the liposome surface and that lysozyme can induce local lipid demixing in POPC/POPG model membranes with formation of lateral domains enriched in negative phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomal leakage test. The assay was performed according to Vechetti et al 65 Briey to prepare DOPC : DOPA (8 : 2) SUV containing calcein trapped within, suitable amount of lipids were dried under nitrogen onto the wall of a Corex glass tube and sonicated with probe-type sonier under nitrogen and controlled temperature. In order to separate calcein-loaded SUV from free dye a Sephadex G-75 was used.…”
Section: Methodsmentioning
confidence: 99%
“…HEWL is also referred as muramidase due to its activity on bacterial cell wall, 45 as well as a membrane disrupter in cell-free system. 46 In this way, it has proved essential to learn whether after the formation of amyloid aggregate, the muramidase and the membrane permeabilization activities are prevalent in the protein. Figure 1e shows the muramidase activity of 1/10 dilution of 1 mg/ml HEWL on Micrococcus lysodecticus alone or in the presence of 0.750 mg/ml heparin.…”
mentioning
confidence: 99%